PENENERAPAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIK SISWA MTS - Novita Anggaraini; Nur Indah Pertiwi; Muhammad Afrilianto (IKIP Siliwangi, 2019)
This research was motivated by the still low mathematical communication skills of MTs Nihayatul Amal Purwasari students. This the purpose of this study is to examine the research of mathematical communication skills of students who learn to use RME.The population in this study were all students of class VIII A MTs Nihayatul Amal Purwasari in Karawang Regency. Data that is processed using SPSS software. So it can be concluded that the results of this study indicate that the Application of the Realistic Mathematic Education (RME) Approach is more effective in improving mathematics learning outcomes, especially in students' mathematical communication skills.